Improving the protection of high-voltage equipment with condenser-type insulation during technical condition monitoring under operating voltage - Sakhno, Oleksandr; Odiyaka, Kostiantyn; Skrupska, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is condenser-type insulation of high-voltage electrical equipment and elements of its overvoltage protection circuits, in the case of breaking the cable to the diagnostic device of technical condition of insulation under operating voltage. The work reports a study on the overvoltage that can cause damage to high-voltage equipment with condenser-type insulation (bushings and instrument current transformers), equipped by hardware for monitoring the technical condition of insulation under operating voltage. Such overvoltage can occur as a result of damage of the cable from the test-tap of the device insulation and/or as a result of lightning and switching overvoltage on the buses of the switchgear. The task relates to insufficient attention and lack of requirements of regulatory documents to the insulation protection schemes of devices with an increase in the number of implementations of devices for monitoring the condition of insulation under operating voltage in recent years. The relevance of the issue is predetermined by war in Ukraine, when electric power facilities and the system as a whole are subject of military attacks, causing both physical destruction and provoking overvoltage and short circuits that affect equipment that has not been destroyed. The paper gives the results of modeling the overvoltage that may arise on the insulation test-tap of equipment with condenser-type insulation, when the cable to the monitoring device is damaged. The results of temperature tests of a complex protective resistor are presented. The use of a parallel resistor and a capacitor as the main protection elements has been justified. Such a scheme could limit the instantaneous overvoltage value for most devices at the level of no more than 1.6 kV, even without the use of additional protection elements, such as varistors or arresters, for example. A methodology and recommendations for selecting protective elements and checking the compliance have been devised, both under the nominal operating mode and in the presence of high-frequency overvoltage